The philosophy book - Buckingham, Will. (London ; New York : DK Pub., 2011)
Examines more than one hundred ideas that have had a significant impact on the history and development of philosophy.
Includes bibliographical references and index.
Adult
Adult
Keywords: Philosophy; Philosophy